2019
DOI: 10.1111/bjd.18168
|View full text |Cite
|
Sign up to set email alerts
|

The association of scalp psoriasis with overall psoriasis severity and koebnerization in children: cross‐sectional findings from the Dutch Child‐CAPTURE registry

Abstract: The authors thank all the clinicians who referred the patients included in this study, the technical teams of the eight laboratories and the French Network of laboratories specialized in molecular diagnosis of CF (GenMucoFrance).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Nevertheless, the Koebner phenomenon is best described in association with psoriasis and there have been a number of studies showing the association of Koebnerization with psoriasis [11,12]. The occurrence of psoriatic lesions at unusual areas of the body regions such as on penis, around eyes, and on keloids suggest that the Koebner phenomenon may be responsible for these psoriatic lesions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the Koebner phenomenon is best described in association with psoriasis and there have been a number of studies showing the association of Koebnerization with psoriasis [11,12]. The occurrence of psoriatic lesions at unusual areas of the body regions such as on penis, around eyes, and on keloids suggest that the Koebner phenomenon may be responsible for these psoriatic lesions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of psoriasis in 402 children (<18 y.o.) as part of the Child-CAPTURE registry (Continuous Assessment of Psoriasis Treatment Use Registry) program showed that the percentage of the affected scalp area was significantly higher in children with a positive Koebner phenomenon vs. children with a negative Koebner phenomenon (50% vs. 25% of the affected scalp, p=0,001) [91]. Scalp psoriasis was observed in 87.6% of children, of whom as much as 35.8% reported scalp psoriasis as the initial place of the disease [91].…”
Section: Mechanical Traumamentioning
confidence: 99%
“…No such associations have been documented for adolescents with psoriasis, with the possible exception to the implication of scratching in the maintenance of scalp psoriasis. 25 Systemic drugs (beta-blockers, lithium, antimalarials, etc.) and HIV infection, are less frequently implicated in the onset of psoriasis in adolescents than they are in adults.…”
Section: Evolution Of the Psoriasis Triggering Factorsmentioning
confidence: 99%
“…Scalp psoriasis has been associated with an increase in the severity of psoriasis and with the Koebner phenomenon, suggesting a possible role for trauma or scratching in the aggravation of scalp psoriasis. 25 In adults, scalp psoriasis is associated with psoriatic arthritis but there are no data confirming such an association in children or adolescents.…”
mentioning
confidence: 99%